1990
DOI: 10.1128/jcm.28.9.1887-1890.1990
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiffusion test for serodiagnosing subcutaneous zygomycosis

Abstract: Culture filtrate antigens of Basidiobolus ranarum and Conidiobolus coronatus were analyzed by immunodiffusion (ID) with homologous rabbit antisera. B. ranarum and C. coronatus were each found to have five specific antigens. Results of tests with heterologous antisera indicated that all of the species shared at least one antigen. ID tests incorporating the specific precipitin bands as references were developed for detection of basidiobolomycosis and conidiobolomycosis. These tests were performed with sera from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 4 publications
1
27
0
3
Order By: Relevance
“…An immunodiffusion test is sensitive and specific for B. ranarum, with no cross-reactivity with other species of the order Entomophthorales, and can be used to monitor its resolution. 2,12 There is no standard treatment for all forms of the disease. Therapeutic trials showed variations in the response rate.…”
Section: Reportmentioning
confidence: 99%
“…An immunodiffusion test is sensitive and specific for B. ranarum, with no cross-reactivity with other species of the order Entomophthorales, and can be used to monitor its resolution. 2,12 There is no standard treatment for all forms of the disease. Therapeutic trials showed variations in the response rate.…”
Section: Reportmentioning
confidence: 99%
“…Conidiobolomycosis can also be identified from clinical tissue samples by PCR (Imhof et al 2003) or by an immunodiffusion test, using serum from the affected horse (Kaufman et al 1990;Steiger and Williams 2000).…”
mentioning
confidence: 99%
“…In microbiologic cultures of C coronatus some conidia show villose appendages, a unique feature that allows definitive diagnosis by differentiating the organism from other zygomycetes reported to infect horses (eg, C lamprauges, B ranarum, and B haptosporus). 3,13,16,17 A recently developed immunodiffusion test helps to identify infection caused by C coronatus. 16 In this test, serum is examined for the precipitation of its antibodies with antigen from C coronatus grown in culture (concentrated cultured filtrate antigen, [CFA]).…”
mentioning
confidence: 99%
“…3,13,16,17 A recently developed immunodiffusion test helps to identify infection caused by C coronatus. 16 In this test, serum is examined for the precipitation of its antibodies with antigen from C coronatus grown in culture (concentrated cultured filtrate antigen, [CFA]). Serum from rabbits immunized with CFA form 5 precipitins with CFA in a control agar, which serves as a reference to identify precipitation lines of diagnostic sera.…”
mentioning
confidence: 99%
See 1 more Smart Citation